2021
DOI: 10.1101/2021.01.26.428356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence signatures of two IGHV3-53/3-66 public clonotypes to SARS-CoV-2 receptor binding domain

Abstract: Since the COVID-19 pandemic onset, the antibody response to SARS-CoV-2 has been extensively characterized. Antibodies to the receptor binding domain (RBD) on the spike protein are frequently encoded by IGHV3-53/3-66 with a short CDR H3. Germline-encoded sequence motifs in CDRs H1 and H2 play a major role, but whether any common motifs are present in CDR H3, which is often critical for binding specificity, have not been elucidated. Here, we identify two public clonotypes of IGHV3-53/3-66 RBD antibodies with a 9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…Somatic mutations in C099 occurred in V geneencoded CDR loops and framework regions (FWRs), while the CDR3 loops remained unchanged from the germline (C098) antibody (Figures S6A and S6E). As previously noted for class 1 anti-RBD neutralizing antibodies (Hurlburt et al, 2020;Tan et al, 2021), somatic mutations in the CDRH1 and CDRH2 of C099 appeared to drive improved binding and neutralizing characteristics. For example, the F27I HC mutation found in C099 introduces a smaller hydrophobic residue that likely makes the CDRH1 loop more flexible, facilitating increased polar contacts and van der Waals interactions in this region (Figures 6C and 6D).…”
Section: Structural Analyses Of Antibody Clonal Pairs Reveal Molecular Contacts That Improve Potency and Breadthsupporting
confidence: 68%
“…Somatic mutations in C099 occurred in V geneencoded CDR loops and framework regions (FWRs), while the CDR3 loops remained unchanged from the germline (C098) antibody (Figures S6A and S6E). As previously noted for class 1 anti-RBD neutralizing antibodies (Hurlburt et al, 2020;Tan et al, 2021), somatic mutations in the CDRH1 and CDRH2 of C099 appeared to drive improved binding and neutralizing characteristics. For example, the F27I HC mutation found in C099 introduces a smaller hydrophobic residue that likely makes the CDRH1 loop more flexible, facilitating increased polar contacts and van der Waals interactions in this region (Figures 6C and 6D).…”
Section: Structural Analyses Of Antibody Clonal Pairs Reveal Molecular Contacts That Improve Potency and Breadthsupporting
confidence: 68%
“…Consistent with the binding mode of class 1 nAbs (Barnes et al, 2020b;Yuan et al, 2020), BG4-25 recognizes an RBD epitope that overlaps with >90% of residues in the ACE2 RBM (Figure S6B), which is only fully accessible with ''up'' RBD conformations. Two V-gene encoded regions in class 1 nAbs prominently contribute to epitope recognition-the 31 SNY 33 CDRH1 and 53 SGGS 56 CDRH2 sequence motifs, which take part in extensive hydrogen bond interactions at the RBD interface ll (Tan et al, 2021;Wu et al, 2020b;Yuan et al, 2020). Analysis of inferred somatic mutations in 93 VH3-53/VH3-66 mAbs coded in our collection of SARS-CoV-2 binding B cells with CDRH3 less than 14 amino acids (IMGT definition) (Lefranc et al, 2015) revealed frequent inferred mutations in these motifs, including S31R and S56T in the Ab heavy chain, which are observed in BG4-25 (Figures S6C-S6E).…”
Section: Vh3-53/vh3-66 Abs With Long Cdrh3s Can Adapt Class 1 Nab Structural Posesmentioning
confidence: 99%
“…Additionally, in vivo studies demonstrated that MD65 effectively elicited post-exposure protection in mice at relatively low doses (Rosenfeld et al, 2021). MD65 (whose variable regions are encoded by the IGHV3-66 and IGKV3-20 germline heavy and light chain alleles, respectively), belongs to a public clonotype (frequently encoded by IGHV3-53/3-66) that was extensively characterized in the context of SARS-CoV-2 neutralizing human antibodies (Barnes et al, 2020; Fagiani et al, 2020; Tan et al, 2021; Yuan et al, 2020), specifically targets the receptor binding motif, competing with hACE2 binding. Noteworthy, recent studies showed that binding and neutralization by antibodies belonging to this public clonotype are weakened by either the K417N or E484K replacements (Andreano et al, 2020; Yuan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%